2014
DOI: 10.1016/j.apgeog.2014.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol plant location and intensification vs. extensification of corn cropping in Kansas

Abstract: Farmers' cropping decisions are a product of a complex mix of socio-economic, cultural, and natural environments in which factors operating at a number of different spatial scales affect how farmers ultimately decide to use their land in any given year or over a set of years. Some environmentalists are concerned that increased demand for corn driven by ethanol production is leading to conversion of non-cropland into corn production (which we label as "extensification"). Ethanol industry advocates counter that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…This industry-wide result was consistent with state-level findings from Kansas, over a comparable time period (2007À2009) [30]. There, corn intensification surrounding ethanol refineries, due to crop switching and an increase in continuous-corn production, was fivetimes greater, by area, than expansion of corn onto new cropland [30]. With respect to uncertainties surrounding feedstock sourcing, as acknowledged in EPA's first triennial report [13], our results are consistent with an argument that U.S. ethanol development has been achieved more so by corn intensification-including crop switching, yield improvements, and continuous-corn productionthan by corn extensification [32].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This industry-wide result was consistent with state-level findings from Kansas, over a comparable time period (2007À2009) [30]. There, corn intensification surrounding ethanol refineries, due to crop switching and an increase in continuous-corn production, was fivetimes greater, by area, than expansion of corn onto new cropland [30]. With respect to uncertainties surrounding feedstock sourcing, as acknowledged in EPA's first triennial report [13], our results are consistent with an argument that U.S. ethanol development has been achieved more so by corn intensification-including crop switching, yield improvements, and continuous-corn productionthan by corn extensification [32].…”
Section: Discussionsupporting
confidence: 87%
“…At the same time, potential ethanol capacity attributable to cropland expansion was modest. This industry-wide result was consistent with state-level findings from Kansas, over a comparable time period (2007À2009) [30]. There, corn intensification surrounding ethanol refineries, due to crop switching and an increase in continuous-corn production, was fivetimes greater, by area, than expansion of corn onto new cropland [30].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This could even be an issue in studies that use an instrumental variables approach, if the instrumental variable is time-invariant and interacted with time effects, such as in Motamed et al (2016). Other studies such as Brown et al (2014) and Blomendahl et al (2011) do not directly address the issue of pre-trends.…”
Section: Production Decisions and Pre-trendsmentioning
confidence: 99%
“…Interviews of Kansas farmers indicate that many farmers support the CRP program and see their participation as important for being a good steward to the land. However, some farmers indicated that they have already converted CRP land to cropland at the end of contracts, or have expressed interest in doing so (Brown et al, 2014;Gray and Gibson, 2013). Farmers cite income potential of grain production and land scarcity as reasons for converting CRP to cultivated land.…”
Section: Expansion Vs Intensification Of Croplandmentioning
confidence: 99%